Functional Properties And Storage Stability Of Alkali Soluble Chicken Meat Protein And Modified Waxy Corn Starch Blend System [QP551. Z63 2007 f rb]. - Zhang, Qian (2007)
The functional properties of alkali soluble chicken meat protein/starch blend were studied in three phases. In the first phase chicken breast meat powder was solubilized with alkali in a 2 × 2 factorial experiment.